Reported Changes in Dietary Behavior Following a First Clinical Diagnosis of Central Nervous System Demyelination - Russell, Rebecca D.; Lucas, Robyn M.; Brennan, Vanessa; Sherriff, Jill L.; Begley, Andrea; , The Ausimmune Investigator Group; Black, Lucinda J.; Chapman, Caron; Coulthard, Alan; Dear, Keith; Dwyer, Terry; Kilpatrick, Trevor; et al. (Frontiers in Neurology, 2018)
Background/Objectives: Although the current evidence is insufficient to recommend a special diet for people with multiple sclerosis (MS), dietary advice for people with MS is prolific online and in the media. This study aimed to describe dietary changes made in the year following a first clinical diagnosis of central nervous system demyelination (FCD), a common precursor to MS. Subjects/Methods: We used follow-up data from the Ausimmune Study, a multicentre matched case-control study examining the environmental risk factors for a FCD. A total of 244 cases (60 male, 184 female) completed a one-year follow-up interview, which included a question about dietary changes. We described the number and proportion (%) of participants who reported making dietary changes and the type of change made. We investigated independent predictors of making a dietary change using a multivariable logistic regression model. Results: A total of 38% (n=92) of participants at the one-year follow up reported making at least one dietary change over the last year. There were no statistically significant independent associations between any participant characteristic and odds of making a dietary change. Of those who made at least one dietary change, the most common changes were increasing fruit and/or vegetable intake (27%, n=25) and following a low-fat diet (25%, n=23). Conclusions: A considerable proportion of the study population reported making at least one dietary change in the year following a FCD, with the majority of changes being towards a healthier diet. Further research is warranted to investigate the reasons behind any dietary changes adopted by people with a FCD or with MS, and whether making a dietary change has benefits for the progression of demyelinating diseases, e.g. to a diagnosis of MS, as well as for general health and well-being.